Editorial (Jonathan Edwards studies, 2013)
We are pleased to commence the third year of the Jonathan Edwards Studies online journal, and continue to be encouraged by the reception and review of the journal and by the contributions we have received from scholars and researchers from all fields, specialists and generalists alike. It is the continuing mission of this journal to present all aspects of Edwards Studies, and more, to encourage inquiry and engagement of Edwards and his context. This issue contains articles on a range of topics, including Edwards’ use of books, his economic thought, and typology, as well as two primary source documents.